Trends in sugar content of non-alcoholic beverages in Australia between 2015 and 2019 during the operation of a voluntary industry pledge to reduce sugar content - Ana-Catarina; Elizabeth Dunford; Alexandra Jones (Cambridge University Press, 2023)
Abstract Objectives: To investigate changes in mean sugar content of non-alcoholic beverages (overall and sugar-sweetened beverages (SSB)) available for purchase in Australia and to compare signatories v. non-signatories of the Australian Beverages Council voluntary pledge from 2018 Design: Retrospective observational study. Setting: Australia. Participants: About 1500 non-alcoholic beverages per year included in the FoodSwitch Monitoring Datasets for 2015-2019. Results: Overall, mean sugar content fell by 1·3 g/100 ml (17·1 %) from 7·5 g/100 ml in 2015 to 6·2 g/100 ml in 2019. SSB have accounted for about 56 % of all beverages available for purchase since 2015. Between 2015 and 2019, the sugar content of SSB dropped by about 10 % (0·8 g/100 ml). Soft drinks and milk-based drinks were the categories with the largest decrease in sugar content. The greater reduction in sugar observed for beverages overall than SSB suggests at least some of the overall decrease in sugar content is due to the appearance of new products with low or no sugar rather than reformulation. Over the same period, beverages with added non-nutritive sweeteners increased from 41 % to 44 %. The decrease in sugar content for all beverages and SSB was, in general, larger for non-signatories than signatories of the voluntary industry pledge. Conclusions: Between 2015 and 2019, the small reduction in sugar content of non-alcoholic beverages in Australia resulted from the combined effects of introducing low- or no-sugar products and reformulation of some categories of SSB. Further policy and regulatory measures are required to reap the most benefit that sugar reduction among non-alcoholic beverages can bring to population health.